Optimizing classroom environments for visually impaired school children a scoping review protocol. - Nur Aresya Ahmad Najmee; Zainora Mohammed; Mohd Harimi Abd Rahman; Norliza Mohamad Fadzil; Arimi Fitri Mat Ludin (PLoS ONE)
Creating a universal and supportive learning environment is essential for the holistic education development of visually impaired school children. However, inadequate infrastructure, limited access to specialized tools, and a shortage of skilled teachers may contribute to lower self-confidence and academic performance. This underscores the necessity for specific guidelines and recommendations to address an optimal classroom setting that is tailored to their visual needs. In this paper, a scoping review protocol is introduced, utilizing the framework proposed by Arksey and O'Malley (2005), to address the following research questions: 1) Is there any established standard classroom setting for visually impaired school children? 2) What recommendations or specific guidelines exist regarding the physical measurement, layout, lighting, contrast, and appropriate position for visually impaired school children? The scoping review explored four electronic databases: PubMed, Scopus Emerald Insight, and Web of Sciences. The outcomes from the scoping review will offer conceptual elucidation, synthesize existing theoretical and empirical understandings, and propose the optimal classroom settings tailored to the visual needs of visually impaired schoolchildren. This paper introduces the a-priori study protocol, which outlines the planned methodology for conducting the scoping review in detail. This protocol has been officially registered with the Open Science Framework (OSF) at the following link: http://osf.io/z2sdt.